Breast, endocrine and surgical oncology - Coventry, Brendon J. (Surgery: Complications, Risks and Consequences, 2014)
Written by internationally acclaimed specialists, Breast, Endocrine and Surgical Oncology provides pertinent and concise procedure descriptions spanning benign and malignant problems and minimally invasive procedures. Complications are reviewed when appropriate for the organ system and problem, creating a book that is both comprehensive and accessible. Stages of operative approaches with relevant technical considerations are outlined in an easily understandable manner. The text is illustrated throughout by photographs that depict anatomic or technical principles. Forming part of the series, Surgery: Complications, Risks and Consequences, this volume Breast, Endocrine and Surgical Oncology provides a valuable resource for all general surgeons and residents in training. Other healthcare providers will also find this a useful resource.